Fluidoterapia como racionalidade em saúde : um estudo sobre a produção de saber do grupo espírita casa da sopa no contexto do cuidado para com o sujeito em situação de rua - Erbereli, Lígia Gomes Rodrigues (2013)
As a result of the urgent need of integration between healthcare and spirituality that the paradigmatic transition impose to us and the consolidation of integrative practices of healthcare, in public spaces, targeted to homeless people, who have relied on the healthcare initiatives, we have formulated the main purpose of this research: to contribute with a production of knowledge that dynamize the latent potentials of integration between healthcare and spirituality, in the context of care of individuals in homelessness situation, carried out by the Spiritist Group Casa da Sopa (GECS). We employed the collaborative research as the method to generate the production of knowledge through reflexive cycles about the care practice of a group-individual, in addition to the gathering of life stories, accordingly to the autobiographical method and the participant observation with registers in the research Journal. The GECS achieved the reflection of the relationship with homeless individuals through the comprehension that place them as spiritual beings, which implicates the admittance of the spirit existence. The Fluid-therapy – therapeutic system that is applied in the care environment of GECS - has theoretical and practical dimensions that characterize it as a complex rationality in healthcare that aims to intertwine social and spiritual care that are interrelated to integrate healthcare and spirituality. Thus, we emphasize elements that contribute to a redefinition of the subject of healthcare practices in a context of production of knowledge that places Fluid-therapy as a rationality in healthcare, set in an emergent paradigm that we name as spirit paradigm.